Development of HTML5-Based Mobile Learning Media to Enhance Critical Thinking Skills of Elementary School Students in IPAS Learning - Himmah, Elok Faiqotul; Astutik, Sri; Aristya, Pramudy Dwi (Jurnal Paedagogy, 2024)
This study aims to examine the validity, practicality, and effectiveness of HTML5-based mobile learning media to enhance the critical thinking skills of elementary school students in science learning (IPAS). The research method used was Research and Development (R&D) with the ADDIE model (analysis, design, development, implementation, evaluation). The study subjects were fourth-grade elementary students from two schools, SDN Yosowilangun Kidul 01 and SDN Yosowilangun Kidul 03 in Lumajang Regency. Data collection techniques included questionnaires, expert validation instruments, practicality instruments, and pretest-posttest data. Data analysis was conducted using a descriptive quantitative approach, focusing on student needs and the validity, practicality, and effectiveness of HTML5-based mobile learning media. The results showed that the HTML5-based mobile learning media had an average validity score of 88.9%, categorized as "highly valid." The practicality test, based on teacher observation and student response questionnaires, yielded an average percentage of 91.50%, categorized as "very practical," indicating that the media is suitable for use in the learning process. In the effectiveness test, the analysis of critical thinking data resulted in an N-gain score of 0.754, categorized as "high," demonstrating that the use of HTML5-based mobile learning media can significantly improve students' critical thinking skills in elementary science learning. In conclusion, the use of HTML5-based mobile learning media in science learning is valid, feasible, and highly effective for improving students' learning outcomes and critical thinking skills at the elementary level.